Web design & Adobe Photoshop - Anderson, Andy (InfiniteSkills, 2012)
"In this training course for Adobe Photoshop, expert trainer Andy Anderson teaches you how to manipulate graphics and video to use on a web site. Since the release of its first version many years ago, Photoshop has added numerous tools tailored for use with graphics destined for the web. In this video tutorial you will learn how to master these tools. This computer based training course demonstrates that Photoshop is capable of more than simply optimizing an image for the web. Andy covers topics ranging from creating a web page mockup to understanding and applying the correct colour type to your images. You will learn about different image formats, which ones you should use, and when. Included are lessons covering vector versus raster imaging, preparing your images for the Internet, and working with layers. Andy even reveals tips and tricks to using Photoshop to create web-friendly videos, making basic animations, generating navigation graphics, and setting up automation and workflow to make you more efficient. Once you have completed this computer based training course on Photoshop for Web Design, you will have a strong grasp of the fundamental tools and capabilities that Photoshop has to offer, and how to apply those tools specifically to your web design related projects. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.